The politics of South India, 1920-1937 - Baker, Christopher John 1948- (Cambridge South Asian studies, 1976)
The interwar years witnessed great changes in the political life of India, with the establishment of new governmental institutions, the emergence of political movements based on class, caste and ideology, and the rapid expansion of the nationalist campaign. This book looks at the complex of political changes during this crucial and formative period in the Madras Presidency, the largest but often the most neglected province of British India. Among the many strands of political life and behaviour which Dr Baker studies are the non-Brahman movement, peasant agitations, caste movements and the rise of the Indian National Congress to a position of undisputed primacy in the region. Making use of hitherto unresearched materials Dr Baker attempts the first overall study of the political process and the dynamics of political change in the province. The book may also be seen as a case-study of political change in a late-colonial society